2022
DOI: 10.1111/cdev.13773
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cross‐racial friendships and children’s social and academic adjustment in racially diverse classrooms

Abstract: This study examined bidirectional associations between cross‐racial friendships and children's social and academic adjustment. Participants were 583 elementary school‐age children in western Canada, or the midwestern United States (4–10 years; 279 girls; 143 Asian, 88 Black, 65 Hispanic or Latinx, 171 White, 116 mixed). Children's adjustment (social preference, academic enablers, academic performance) and friendship nominations (reciprocated, received, given) were measured in fall and spring over one school ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…There are also methodological challenges that may complicate findings in this area of research. With a few exceptions (Qi et al, 2022), there has been a paucity of longitudinal findings that could shed light on the temporal ordering of the relations. Moreover, investigators have tended to rely on single-index assessments of social adjustment, which did not fully capture positive peer regard as a multifaceted construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also methodological challenges that may complicate findings in this area of research. With a few exceptions (Qi et al, 2022), there has been a paucity of longitudinal findings that could shed light on the temporal ordering of the relations. Moreover, investigators have tended to rely on single-index assessments of social adjustment, which did not fully capture positive peer regard as a multifaceted construct.…”
Section: Discussionmentioning
confidence: 99%
“…Kawabata and Crick (2015) reported a positive concurrent association between cross-ethnic friendship and academic engagement from a racially diverse sample of elementary students. Longitudinal studies have suggested possible bidirectional relationships between friendships in multiethnic schools and academic outcomes, though some controversy may exist (Lewis et al, 2018; Qi et al, 2022; Witkow & Fuligni, 2010). Given the adaptive correlates of having cross-ethnic friends (e.g., social-cognitive skills and cooperative learning skills; Lease & Blake, 2005; Rucinski et al, 2021), cross-ethnic friendship has been proposed to play a more salient role in academic functioning above and beyond friendship with same-ethnic peers (Kawabata & Crick, 2015).…”
Section: Ethnicity Achievement and Peers During Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…Due to its strong psychometric properties, the ACES-SF has also been used in a recent study (Monopoli et al, 2023) to evaluate convergent and discriminant validity for the Social Experiences Questionnaire (SEQ; developed by Crick & Grotpeter, 1996), a measure of peer victimization. In addition to psychometric studies, the Academic Enablers scale of the ACES-SF has been utilized in applied research with both typically developing student populations as well as students at risk for psychopathology (e.g., Mikami et al, 2022; Qi et al, 2022).…”
Section: Academic Competence Evaluation Scales–short Form (Aces-sf)mentioning
confidence: 99%